2006
DOI: 10.1073/pnas.0507604103
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic Bid is required for pulmonary fibrosis

Abstract: The molecular mechanisms of pulmonary fibrosis are poorly understood. Previous reports indicate that activation of TGF-␤1 is essential for the development of pulmonary fibrosis. Here, we report that the proapoptotic Bcl-2 family member Bid is required for the development of pulmonary fibrosis after the intratracheal instillation of bleomycin. Mice lacking Bid exhibited significantly less pulmonary fibrosis in response to bleomycin compared with WT mice. The attenuation in pulmonary fibrosis was observed despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 36 publications
3
108
0
3
Order By: Relevance
“…In addition to endothelin-1 induction, TGF-b1 may induce fibrosis by activating caspases that mediate cell death and apoptosis. In one study, investigators found that Bax and Bid, two apoptotic regulatory proteins suggested to mediate fibrotic responses (57,58), may be activated by TGF-b1 and may facilitate bleomycin-induced pulmonary fibrosis in mice (59). In this study, TGF-b1-mediated increases in inflammation, lung collagen content, and lung cell apoptosis were decreased significantly in both Bax-and Bid-null mice versus wild-type control mice.…”
Section: Airway Remodeling and Proliferationmentioning
confidence: 52%
“…In addition to endothelin-1 induction, TGF-b1 may induce fibrosis by activating caspases that mediate cell death and apoptosis. In one study, investigators found that Bax and Bid, two apoptotic regulatory proteins suggested to mediate fibrotic responses (57,58), may be activated by TGF-b1 and may facilitate bleomycin-induced pulmonary fibrosis in mice (59). In this study, TGF-b1-mediated increases in inflammation, lung collagen content, and lung cell apoptosis were decreased significantly in both Bax-and Bid-null mice versus wild-type control mice.…”
Section: Airway Remodeling and Proliferationmentioning
confidence: 52%
“…Assessment of Lung Permeability-Lung permeability was assessed using a modification of a described previously tech-nique (26). The mice were anesthetized with pentobarbital, and 125 l of fluorescein isothiocynate-dextran (molecular mass, 4,000 kDa) 0.05 g/ml (Sigma-Aldrich) was delivered into the retro-orbital plexus using a 26-gauge needle.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting-Protein immunoblotting was performed as described previously (26). The cell lysates were mixed with sample loading buffer (125 mM Tris base (pH 6.8), 4% (w/v) SDS, 20% (v/v) glycerol, 200 mM dithiothreitol, 0.02% (w/v) bromphenol blue).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Programmed cell death or apoptosis is a highly regulated process of cell removal in which tissue architecture is preserved and inflammation is minimized (Allen et al, 1997). To date, a considerable body of research has shown that alveolar apoptosis is a critical determinant in the pathways that initiate fibrogenesis in the lung (Adamson et al, 1988;Hagimoto et al, 1997aHagimoto et al, , 1997bRuiz et al, 2003;Budinger et al, 2006;Uhal et al, 1995 and. There are two pathways for regulating caspase activation: one is wellcharacterized and coupled to cell death receptors, and the other is initiated by events that are less clear and involve the release of mitochondrial cytochrome c. The release of cytochrome c from the mitochondria during apoptosis is regulated by members of the family of Bcl-2 related proteins.…”
Section: Discussionmentioning
confidence: 99%